Sociological perspectives of health and illness - Phellas, Constantinos N. (Cambridge Scholars, 2010)
Medical sociology has evolved from being considered as unimportant area of enquiry to being regarded as in the centre of the study of private troubles and public issues. At the present much of what is deemed in sociology as exciting is gaining or contribu.